PRELIMINARY INSIGHTS ON THE ACEHNESE DAILY STRESSORS IN CONFLICT AFFECTED AREA - Fairuziana Humam Hamid; Gloryka Ednadita (Universitas Ahmad Dahlan, 2020)
The 2005 peace memorandum was a significant event for the development of Aceh province, following 30 years living in the adversity of political conflict and violence. Persistent stress in post-conflict communities may occur due to daily life hardships related to economic and political instability, such as access to education, employment, and others. These stresses are referred to as daily stressors. The purpose of this study is to explore the daily stressors among the Acehnese 13 years following the peace memorandum. The study was conducted in the city center of North Aceh, one of the regencies that were highly affected by political conflict and violence. We recruited 20 participants with convenience sampling that were consisted of village headmen and local villagers from one of the villages in North Aceh, Alue Anoe Timu. The study employed qualitative design by collecting data with focus group discussion and data were analyzed with thematic analysis. The results are discussed and may provide meaningful knowledge to the development of conflict-affected areas in Aceh.Â